Graziaedessa anastrephae (Heteroptera: Pentatomidae: Edessinae) a new genus and species collected in Multilure® fruit fly traps baited with ammonium acetate and putrescine - Eger, Joseph E. (Zootaxa, 2021)
Graziaedessa anastrephae (Heteroptera: Pentatomidae: Edessinae) a new genus and species collected in Multilure® fruit fly traps baited with ammonium acetate and putrescine. During a survey for fruit flies (Anastrepha spp., Diptera, Tephritidae) in Peru, specimens of a previously undescribed genus and species of Edessinae were collected in Multilure® fruit fly traps baited with a combination of ammonium acetate and putrescine. The new taxon, Graziaedessa anastrephae n. g., n. sp., resembles species of the edessine genus Hypoxys Amyot & Serville but is smaller and the thoracic sternal structure is unique, consisting of an enlarged metasternal process which is bifurcate posteriorly but simple and rounded anteriorly, reaching for a short length onto the mesosternum and continued by a mesial carina on the mesosternum. Graziaedessa n. g. and G. anastrephae n. sp. are described and figured and compared to other genera of Edessinae.